Digital customer success why the next frontier of CS is digital and how you can leverage it to drive durable growth - Mehta, Nick 1977-; Capote, Kellie (John Wiley & Sons, Ltd, 2024)
"Customer Success has evolved and matured immensely over the past decade and now palys a mission-critical role for many organizations--helping them train and retain their customers. It is a critical growth engine for organizations, widely accepted by executives, investors, and consultancies alike. The problem is, Customer Success requires hiring and training expensive Customer Success managers, who may not be available when customers need help. The answer to this probelm, and the next stage of the entire Customer Success movement is Digital Customer Success-- designing digital interventions that help software users learn and grow as they use your software-- without needing to schedule a meeting with a live Customer Success Manager. This book provides a detailed "How To" guide to Digital Customer Success to ensure you can meet the needs of your customers, investors and teammates. Learn the basics of Digital Customer Success Maturity model and the core tenets of how to get started, ideal organizational structures, success measurements and more. We will also showcase learnings and tips from organizaitons who are paving the way with their digital customer success strategies"--
Includes index. - Description based on online resource; title from digital title page (viewed on June 11, 2024)
Keywords: Business enterprises -- Technological innovations; Success in business; Customer relations; Customer services; Entreprises; Innovations; Succès dans les affaires; Service à la clientèle